Toward improved survivorship: supportive care needs of esophageal cancer patients, a literature review. Issue 8 (1st December 2016) - Graham, L.; Wikman, A.
Summary: The growing prevalence of esophageal cancer survivors represent a population typified by an extensive treatment regime, significant postsurgical long-term effects, and a dismal prognosis. Despite this, little is known of the supportive care needs of this patient group and the extent to which these are being met in practice. This review provides a synthesis of the research evidence to date; emphasizing opportunities for clinical application and setting a future agenda with research priorities. A literature search was performed using Medline/Embase, PsycINFO, and Web of Science. Search headings used included; [esophagus] or [esopohageal] or [upper gastrointestinal] or [upper GI] AND [cancer] or [carcinoma] or [squamous cell] AND [supportive care] or [survivorship] or [psychological] or [emotional] or [information] or [social] or [communication] or [spiritual] or [health-related-quality-of-life] or [HRQL] or [qualitative] or [patient narrative] or [clinical nurse specialist] or [CNS]. Related articles in English were reviewed, with additional articles harvested from reference sections. Esophageal cancer survivors report significant late-term effects posttreatment, encompassing sustained impairment in most areas of health-related quality of life. With a necessitated change in eating behavior, survivors find it particularly challenging to adjust to a new social identity and as a cancer population report high levels of psychological morbidity. Although the determinants of psychological morbidity are largely unknown, illness representations may be a key contributor. Several multidisciplinary supportive care interventions have been developed with promising results. The research summarized in this paper provides valuable insight into the psychosocial well-being of the esophageal cancer survivor. However, knowledge gaps remain, alongside a dearth of applied examples in meeting supportive care need.